Oxytocin, vasopressin, and Williams syndrome: epigenetic effects on abnormal social behavior - Haas, Brian W.; Smith, Alicia K. (Frontiers in Genetics, 2015)
Williams syndrome is a condition caused by a deletion of 26-28 genes on chromosome 7q11.23 often characterized by abnormal social behavior and disrupted oxytocin and vasopressin functioning. The observation that individuals with Williams syndrome exhibit oxytocin and vasopressin dysregulation is compelling. There is currently a lack of evidence that any of the genes typically deleted in Williams syndrome have any direct effect on either oxytocin or vasopressin. In this perspective article, we present a novel epigenetic model describing how DNA methylation may impact the expression of key genes within the oxytocin and vasopressin systems, which may ultimately influence the social behavior observed in Williams syndrome. We draw support from data pooled from a prior empirical research study (Henrichsen, et al., 2011), demonstrating that OXTR is overexpressed in Williams syndrome. These preliminary findings may create new opportunities to target the oxytocin and vasopressin systems with the specific goal of improving outcomes in Williams syndrome and other psychiatric conditions.